The NAC transcription factor FaRIF controls fruit ripening in strawberry. - Martín-Pizarro, Carmen; Vallarino, José G.; Osorio-Algar, Sonia; Meco, Victoriano; Urrutia, María; Pillet, Jeremy; Casañal, Ana; Merchante-Berg, Catharina; Amaya, Iraida; Willmitzer, Lothar; Fernie, Alisdair R.; Giovannoni, James J.; et al. (Oxford University Press [University Publisher], American Society of Plant Biologists [Society Publisher], 2021)
In contrast to climacteric fruits such as tomato, the knowledge on key regulatory genes controlling the ripening of strawberry, a nonclimacteric fruit, is still limited. NAC transcription factors (TFs) mediate different developmental processes in plants. Here, we identified and characterized Ripening Inducing Factor (FaRIF), a NAC TF that is highly expressed and induced in strawberry receptacles during ripening. Functional analyses based on stable transgenic lines aimed at silencing FaRIF by RNA interference, either from a constitutive promoter or the ripe receptacle-specific EXP2 promoter, as well as overexpression lines showed that FaRIF controls critical ripening-related processes such as fruit softening and pigment and sugar accumulation. Physiological, metabolome, and transcriptome analyses of receptacles of FaRIF-silenced and overexpression lines point to FaRIF as a key regulator of strawberry fruit ripening from early developmental stages, controlling abscisic acid biosynthesis and signaling, cell-wall degradation, and modification, the phenylpropanoid pathway, volatiles production, and the balance of the aerobic/anaerobic metabolism. FaRIF is therefore a target to be modified/edited to control the quality of strawberry fruits.
Keywords: Fresas - Maduración; Genética vegetal; Strawberry; Fruit ripening; Quality; Transcription factor